Hekla 1947, 1845, 1510 and 1158 tephra in Finland: challenges of tracing tephra from moderate eruptions - Maarit Kalliokoski; Esther Ruth Guðmundsdóttir; Stefan Wastegård (WILEY, 2022)
Several cryptotephra layers that originate from Icelandic volcanic eruptions with a volcanic explosivity index (VEI) of <= 4 and tephra volumes of < 1 km3 have previously been identified in Northern Europe, albeit within a restricted geographical area. One of these is the Hekla 1947 tephra that formed a visible fall-out in southern Finland. We searched for the Hekla 1947 tephra from peat archives within the previously inferred fall-out zone but found no evidence of its presence. Instead, we report the first identification of Hekla 1845 and Hekla 1510 cryptotephra layers outside of Iceland, the Faroe Islands, Ireland and the UK. Additionally, Hekla 1158 tephra was found in Finland for the first time. Our results confirm that Icelandic eruptions of moderate size can form cryptotephra deposits that are extensive enough to be used in inter-regional correlations of environmental archives and carry a great potential for refining regional tephrochronological frameworks. Our results also reveal that Icelandic tephra has been dispersed into Finnish airspace at least seven times during the past millennium and in addition to a direct eastward route the ash clouds can travel either via a northerly or a southerly transport pathway.